Sex-Specific Factors Associated With Suicidal Ideation Among Individuals With Type 2 Diabetes: A Cross-Sectional Study - Jieun Lee; Suhyeon Hwang; Hyon-Seung Yi; Junglyun Kim (Western Journal of Nursing Research, 2026)
Background: Type 2 diabetes (T2D) is a chronic metabolic disease linked to mental health issues, including suicidal ideation. Despite growing concern, limited research has explored the sex-specific biological and psychosocial risk factors contributing to suicidal ideation in this population. Objective: We sought to identify sex-specific factors associated with suicidal ideation in individuals with type 2 diabetes. Methods: A cross-sectional study was conducted with 695 adults diagnosed with T2D at a university hospital outpatient clinic between May 2022 and April 2023. Clinical and laboratory data were obtained from electronic health records. Suicidal ideation and fatigue were assessed using self-reported questionnaires. Multiple logistic regression was performed using SPSS 30.0 to identify sex-specific factors. Results: Among the 695 participants, the mean age was 60.5 (SD = 11.8), and 406 (58.4%) were men. In men, being married (adjusted odds ratio [AOR] = 4.54) and reporting higher fatigue (AOR = 1.44) were associated with suicidal ideation, while living with someone was associated with lower suicidal ideation (AOR = 0.16). In women, elevated creatinine (AOR = 11.69), smoking (AOR = 10.84), and higher fatigue (AOR = 1.43) were significantly associated with suicidal ideation. Conclusion: Marriage is significantly associated with suicidal ideation, while living with someone protects from suicidal ideation in men. Elevated creatinine and smoking are associated with higher suicidal ideation in women. Fatigue emerged as a consistently associated factor of suicidal ideation. The findings highlight the need for tailored suicide risk screening and for interpreting the influence of social support by gender. Fatigue management is crucial for the prevention of suicide among individuals with T2D.